Victorian Jamaica - Modest, Wayne; Barringer, T. J. (Book collections on Project MUSE., 2018)
Victorian Jamaica explores the extraordinary surviving archive of visual representation and material objects to provide a comprehensive account of Jamaican society during Queen Victoria's reign over the British Empire, from 1837 to 1901. In their analyses of material ranging from photographs of plantation laborers and landscape paintings to cricket team photographs, furniture, and architecture, as well as a wide range of texts, the contributors trace the relationship between black Jamaicans and colonial institutions; contextualize race within ritual and performance; and outline how material and visual culture helped shape the complex politics of colonial society. By narrating Victorian history from a Caribbean perspective, this richly illustrated volume--featuring 270 full-color images--offers a complex and nuanced portrait of Jamaica that expands our understanding of the wider history of the British Empire and Atlantic world during this period.